2003
DOI: 10.1002/bem.10075
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarised MF (500 μT 50 Hz) does not acutely suppress melatonin secretion from cultured Wistar rat pineal glands

Abstract: Magnetic fields (MF, 50 Hz) have been proposed to affect melatonin production in mammals; however, there is very little data about the mechanism by which this possible interaction may occur. Here we describe results from the first study in which circularly polarised 50 Hz MF have been administered to isolated pineals in highly controlled conditions. Melatonin release from isolated Wistar rat pineal glands, dissected 2 h after light onset ZT 2, was measured in a flow through culture system, during and after exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The value of the cutoff should be optimized using a trial-and-error procedure. In our study, we used LR with variable selection method to predict melatonin excretion Tripp et al [2003] patterns in the rat exposed to ELF-MF. A tolerance filter of 0.5 was also used to avoid multicollinearity, and thus avoid the mutually correlated variables being incorporated into the final regression equation.…”
Section: Logistic Regression (Lr)mentioning
confidence: 99%
“…The value of the cutoff should be optimized using a trial-and-error procedure. In our study, we used LR with variable selection method to predict melatonin excretion Tripp et al [2003] patterns in the rat exposed to ELF-MF. A tolerance filter of 0.5 was also used to avoid multicollinearity, and thus avoid the mutually correlated variables being incorporated into the final regression equation.…”
Section: Logistic Regression (Lr)mentioning
confidence: 99%
“…A reduction in isoproterenol-stimulated melatonin secretion and activity of arylalkylamine N-acetyltransferase has also been found in studies of rat pinealocytes after exposure to ELF-MF [96, 97]. On the contrary, Lewy et al [98] noted increased activity of melatonin-synthetizing enzymes, while Tripp et al [99] found no changes in melatonin secretion in rat pinealocytes in response to ELF-MF.…”
Section: Effects Of Electric Magnetic and Electromagnetic Fieldsmentioning
confidence: 87%
“…In vitro studies concerning the effect of electromagnetic fields on melatonin secretion were conducted on the pineal glands of Djungarian hamsters [95, 100] and rats [9699]. The results of experiments with hamster pineals in the superfusion organ culture demonstrated that ELF-MF with an intensity of 86  μ T and a frequency of 16.67 or 50 Hz caused a decrease in melatonin secretion, activated by isoproterenol [95].…”
Section: Effects Of Electric Magnetic and Electromagnetic Fieldsmentioning
confidence: 99%
“…Various in vivo, in vitro, human experimental and epidemiological studies carried out to identify effects of electromagnetic fields on melatonin are reviewed in as shown in table 1 and 2. [12] REVIEW ARTICLE Table-1: Studies of the effects of magnetic fields on melatonin production Exposure Effect 'Ion-cyclotron resonance' for calcium [13] NA stimulation of melatonin production and release reduced 50 μT, 60Hz for 12 h [14] NA stimulation of melatonin release reduced 1 mT, 50Hz for 1 h [15] NAT activity decreased 86 μT, 50Hz or 16.67 Hz for 8 h [16] Isoproterenol stimulation of melatonin production reduced 1 mT, 50Hz for 4h [17] NA stimulation of melatonin release increased 0.5 mT, 50 Hz for 4h [18] No effect on melatonin release [19,20] EMF exposure partially blocked melatonin (10 -9 M) inhibition in MCF-7 cells, Similar result with tamoxifen (10 -7 M) 1.2 μT, 60Hz for 7 days [21] EMF exposure partially blocked temoxifen (2.5 10 -8 M) inhibition of MCF-7 cells 1.2 or 100 μT, 50Hz for 7 days [22] Inhibition of DNA synthesis by melatonin (10 -11 M) partially blocked by 1.2 µT EMF exposure. 100 µT blocked cAMP inhibition by melatonin (10 -9 M) in MCF-7 celss 0.3 mT pulsed for 20ms at 2 Hz for 1 h repeated over 3 days [23] Growth of MCF-7 cells unaffected…”
Section: General Physiologymentioning
confidence: 99%